Peran Reputasi Kap Memoderasi Pengaruh Komite Audit, Audit Tenure, dan Profitabilitas Terhadap Audit Report Lag - Weni, Weni; Desyana, Gita; Muhsin, Muhsin (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study was to test and analyze the effect of audit committee, audit tenure and profitability on audit report lag with KAP reputation as moderation. The object of this research is food and beverage subsector companies listed on the IDX for the period 2020-2023. The sampling technique was purposive sampling, 52 samples were obtained. The research method is quantitative with the data analysis techniques used consisting of descriptive analysis, panel data model regression method test, classical assumption test, moderated regression analysis (MRA) test, coefficient of determination test and partial test (T) with the help of EViews 12 software. The variables of this study consist of audit committee, audit tenure, profitability, KAP reputation, and audit report lag. The results showed that the audit committee had a positive effect on audit report lag, audit tenure had no effect on audit report lag, profitability had a positive effect on audit report lag, hood reputation was unable to moderate the relationship between audit committee, audit tenure and profitability on audit report lag.